2011
DOI: 10.3390/pharmaceutics3040923
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Duration and Amplitude of Direct Current when Lidocaine Is Delivered by Iontophoresis

Abstract: Dosage for the galvanic stimulation for iontophoresis varies. Clinicians manipulate the duration or the amplitude of the current, but it is not known which is more effective. We compared the anesthetic effect of lidocaine HCL (2%) by manipulating the current parameters on 21 healthy volunteers (age: 21.2 ± 4.2, height 170.7 ± 10.2 cm, mass 82.1 ± 19.2 kg). Three conditions were administered in a random order using a Phoresor II® with 2 mL, 2% lidocaine HCL in an iontophoresis electrode. (1) HASD (40 mA*min): H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…All electrode starting impedance were below 100 KΩ. Due to the iontophoretic mechanisms ( Prausnitz, 1996 ), lidocaine was delivered to minimize physical perception of current stimulation at the scalp ( Saliba et al, 2011 ), and electrode-scalp impedances were reduced over time as well ( Oh and Guy, 1995 ). Note that with the constant current multichannel AccuCharge Circuit, the desired current level is maintained even as impedances drop with continued skin hydration.…”
Section: Methodsmentioning
confidence: 99%
“…All electrode starting impedance were below 100 KΩ. Due to the iontophoretic mechanisms ( Prausnitz, 1996 ), lidocaine was delivered to minimize physical perception of current stimulation at the scalp ( Saliba et al, 2011 ), and electrode-scalp impedances were reduced over time as well ( Oh and Guy, 1995 ). Note that with the constant current multichannel AccuCharge Circuit, the desired current level is maintained even as impedances drop with continued skin hydration.…”
Section: Methodsmentioning
confidence: 99%
“…Using this system of iontophoresis, antibiotics and nonsteroidal anti-inflammatory drugs (NSAIDs) can be administered in order to alleviate inflammation and pulpal pain or dentine hypersensitivity following bleaching or acid etching of enamel [51,82]. Saliba et al demonstrated that high amplitude/short duration or low amplitude/long duration of lidocaine iontophoresis does not affect the anesthetic level when the same dosage is applied [83].…”
Section: Local Anestheticsmentioning
confidence: 99%
“…Iontophoresis (IOP) is a physical transdermal drug enhancement technique, which uses electric potential to drive the drug ions through biological membrane. Many studies have reported the use of IOP technique to enhance the lidocaine HCL transportation both in vitro & in vivo and in clinical settings at current density up to 0.5 mA/cm 2 However, most of the in vitro and in vivo lidocaine HCL permeation studies were conducted across artificial membrane and other animals like rats, mice and porcine skin. To our knowledge, very limited lidocaine HCL permeation studies were conducted using human skin .…”
Section: Introductionmentioning
confidence: 99%